HBsAg isoform dynamics during NAP‐based therapy of HBeAg‐negative chronic HBV and HBV/HDV infection. Issue 8 (2nd April 2022) - Bazinet, Michel; Anderson, Mark; Pântea, Victor; Placinta, Gheorghe; Moscalu, Iurie; Cebotarescu, Valentin; Cojuhari, Lilia; Jimbei, Pavlina; Iarovoi, Liviu; Smesnoi, Valentina; Musteata, Tatina; Jucov, Alina; et al.
Abstract: Nucleic acid polymers block the assembly of hepatitis B virus (HBV) subviral particles, effectively preventing hepatitis B surface antigen (HBsAg) replenishment in the circulation. Nucleic acid polymer (NAP)–based combination therapy of HBV infection or HBV/hepatitis D virus (HDV) co‐infection is accompanied by HBsAg clearance and seroconversion, HDV‐RNA clearance in co‐infection, and persistent functional cure of HBV (HBsAg < 0.05 IU/ml, HBV‐DNA target not dected, normal alanine aminotransferase) and persistent clearance of HDV RNA. An analysis of HBsAg isoform changes during quantitative HBsAg declines (qHBsAg), and subsequent treatment‐free follow‐up in the REP 301/REP 301‐LTF (HBV/HDV) and REP 401 (HBV) studies was conducted. HBsAg isoforms were analyzed from frozen serum samples using Abbott Research Use Only assays for HBsAg isoforms (large [L], medium [M], and total [T]). The relative change over time in small HBsAg relative to the other isoforms was inferred by the change in the ratio over time of T‐HBsAg to M‐HBsAg. HBsAg isoform declines followed qHBsAg declines in all participants. No HBsAg isoforms were detectable in any participants with functional cure. HBsAg declines > 2 log10 IU/ml from baseline were correlated with selective clearance of S‐HBsAg in 39 of 42 participants. Selective S‐HBsAg decline was absent in 9 of 10 participants with HBsAg decline < 2 log10 IU/ml from baseline. Mild qHBsAg rebound during follow‐up <10 IU/ml consisted mostly of S‐HBsAg and M‐HBsAg and not accompanied by significant covalently closed circular DNA activity. Conclusion: The faster observed declines in S‐HBsAg indicate the selective clearance of subviral particles from the circulation, consistent with previous mechanistic studies on NAPs. Trace HBsAg rebound in the absence of HBV DNA may reflect HBsAg derived from integrated HBV DNA and not rebound of viral infection. Abstract : Selective declines in the small isoform of HBsAg during therapy indicate the targeting of HBV subviral particles. Selective declines in the small isoform of HBsAg are observed during therapy with nucleic acid polymers, consistent with their selective targeting of the assembly and secretion of subviral particles observed in vitro and in vivo .image